Serological responses of Guinea pigs and heifers to eight different BoAHV-1 vaccine formulations - Camargo, Luana (2024)
Bovine alphaherpesvirus 1 (BoAHV-1) infection affects the production and reproductive performance of dairy and beef livestock, resulting in considerable economic losses. In addition to biosecurity measures, vaccination programs are effective strategies for controlling and preventing BoAHV-1 infection and transmission. We evaluated the serological immune response against BoAHV-1 induced by eight different formulations of commercial vaccines: three modified live vaccines and five killed vaccines containing BoAHV type 1 or types 1 and 5. In the first experiment, 50 BoAHV-1-seronegative guinea pigs were assigned to eight groups; each individual in the treatment groups received two doses (one-fifth of the bovine dose). The second experiment was conducted using 29 crossbred Holstein × Gir heifers in four groups of six to nine animals each. The serological immune response against BoAHV-1 was measured using virus neutralization and enzyme-linked immunosorbent assays to measure the total IgG against BoAHV. We evaluated the effects of the vaccine, time, and interaction of the vaccine and time on neutralizing antibodies against BoAHV-1. Killed vaccines produced low levels of antibodies against BoAHV-1, whereas modified live vaccines produced high levels of antibodies capable of providing neutralizing titers in the vaccinated animals, with the thermosensitive modified live vaccine showing the highest levels of antibodies.